Effect of arbuscular mycorrhizal fungi on the physiological functioning of maize under zinc-deficient soils - Saboor, Abdul; Ali, Muhammad Arif; Danish, Subhan; Ahmed, Niaz; Fahad, Shah; Datta, Rahul; Ansari, Mohammad Javed; Nasif, Omaima; Rahman, Muhammad Habib Ur; Glick, Bernard R (Scientific reports, 2021)
Zinc (Zn) deficiency can severely inhibit plant growth, yield, and enzymatic activities. Zn plays a vital role in various enzymatic activities in plants. Arbuscular mycorrhizal fungi (AMF) play a crucial role in improving the plant's Zn nutrition and mitigating Zn stress effects on plants. The current study was conducted to compare the response of inoculated and non-inoculated maize (YH 1898) in the presence of different levels of zinc under greenhouse conditions under a Zn deficient condition. There were two mycorrhizal levels (i.e., M + with mycorrhizae, M- without mycorrhizae) and five Zn levels (i.e., 0, 1.5, 3, 6, and 12 mg kg-1), with three replicates following completely randomized design. At the vegetative stage (before tillering), biochemical, physiological, and agronomic attributes were measured. The results showed that maize plants previously inoculated with AMF had higher gaseous exchange traits, i.e., a higher stomatal conductance rate, favoring an increased photosynthetic rate. Improvement in antioxidant enzyme activity was also observed in inoculated compared to non-inoculated maize plants. Moreover, AMF inoculation also played a beneficial role in nutrients availability and its uptake by plants. Higher Zn12 (12 mg Zn kg-1 soil) treatment accumulated a higher Zn concentration in soil, root, and shoot in AMF-inoculated than in non-inoculated maize plants. These results are consistent with mycorrhizal symbiosis beneficial role for maize physiological functioning in Zn deficient soil conditions. Additionally, AMF inoculation mitigated the stress conditions and assisted nutrient uptake by maize.
Keywords: Photosynthesis; Zea mays; průduchy rostlin; kukuřice setá; půda; Soil; mykorhiza; fotosyntéza; Zinc; Mycorrhizae; zinek; Plant Stomata